PEMANFAATAN TEKNOLOGI PERKANTORAN DALAM MENINGKATKAN KETRAMPILAN SISWA SMK PGRI 1 JAKARTA TIMUR - Faridah, Faridah; Rahmadhani, May Vitha; Yoeliastuti, Yoeliastuti; Indriany, Yunita; Sintesa, Nika (JURNAL ABDIMAS PLJ, 2023)
Increasingly sophisticated technology has resulted in the development of system technology in the field of administrative work in various agencies to become more effective and efficient, from light to complex administrative work. However, this must be balanced with abilities and skills that support their development. To face this progress, the world of work must always change. There are 2 things that can be done to meet these demands, namely providing competent human resources in the field of office technology, as well as providing supporting infrastructure. LP3I Jakarta Polytechnic takes part in optimizing students' abilities and skills in forming productive personnel in the field of office technology through community service activities. The aim of this activity is to make the transition to working life safer for vocational school students. The method used is the lecture method, delivery of material and discussion. The result of the service is providing useful provisions such as changing students' mindsets about their soft skills, the importance of understanding technological developments, changing behavior, and increasing knowledge about office machines. The conclusion of this service is that it provides benefits for students to become more confident and ready to compete, as productive workers in the business world. LP3I Polytechnic lecturers can use it as a place to distribute knowledge and knowledge that is beneficial to society. Keywords: Optimization; Office Technology; Knowledge